2014
DOI: 10.12988/cems.2014.456
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-sparing effect of tacrolimus in the maintenance phase of systemic lupus erythematosus: a single-center, prospective study

Abstract: 76Yusuke Miwa et al. AbstractObjective: The purpose of this study was to prospectively assess the steroid-sparing effect and safety of Tacrolimus (TAC) combination treatment during the maintenance phase of SLE.Methods: Thirty-eight patients were studied over a 1-year period from 2009 to 2012. If manifestations of mild active SLE, such as skin eruptions, arthritis, or asymptomatic nephritis, worsened and/or decreasing levels of serum complement (C3c) were observed, TAC combination treatment (from 1 mg to 5 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 19–21 Maintenance therapy of SLE was previously reported only in studies of patients with or without lupus nephritis, 12 13 22 including one small group study and one short-duration study. 14 15 No previous assessments of long-term TAC therapy were reported in a larger group of patients with SLE with and without renal complications, as performed in this study. We investigated whether renal complication affected the efficacy and safety of TAC combination therapy in patients with SLE during a maintenance phase.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 19–21 Maintenance therapy of SLE was previously reported only in studies of patients with or without lupus nephritis, 12 13 22 including one small group study and one short-duration study. 14 15 No previous assessments of long-term TAC therapy were reported in a larger group of patients with SLE with and without renal complications, as performed in this study. We investigated whether renal complication affected the efficacy and safety of TAC combination therapy in patients with SLE during a maintenance phase.…”
Section: Discussionmentioning
confidence: 92%
“…For example, one small-scale study reported an approximately 6-month observation period, 14 and a clinical practice report of 38 cases used TAC for 1 year. 15 However, there have not been reports of a large-scale clinical practice study, such as the inclusion of more than 50 cases followed up for 1 year. However, one report suggested that the long-term use of TAC caused renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%